Relationship between phosphates mineralogy and mineral processing - The case of Greece - Anastassakis, G. (Bulletin of the Geological Society of Greece, 2013)
Phosphorus is one of the most important elements for life and growth of plants, animals and humans. Its absence or depletion from the soil necessitates their addition in the form of fertilizers. The only realistic source of elemental phosphorus and phosphoric fertilizers on commercial scale is phosphate rock. The importance of phosphate rocks becomes greater by taking into account that phosphorus can’t be obtained by recycling processes as well as that there are no substitutes for it in agriculture. In most cases, phosphate deposits have to be processed in order to meet the commercial requirements. In the current paper, it is presented the various forms of phosphate deposits, the participating minerals in each case and the effect of mineralogical composition on the beneficiation method applied. Finally, details on the phosphate deposits of Greece are presented, their mineralogy, and the possibility of their beneficiation.